FEATURES OF CREATING A HOTEL MANAGEMENT INFORMATION SYSTEM - VASYLIUK, ANDRII; STRUS, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article describes the problems associated with the formation of an effective medium of information in managerial interaction. The main problems and obstacles of the use of information flows in the activities of hospitality enterprises have been identified. The most important information processes that take place in accommodation facilities through the implementation of business processes have been determined. The structure of the information flow of the hotel enterprise and the most important modern information technologies, which are a carrier of information for management activities, are characterized. An analysis of hotel projects implemented in Ukraine on the basis of HMS of various brands is provided. An assessment of the content, completeness and intensity of information content was carried out with the determination of the index of consumer satisfaction with the main services of hotel enterprises. The peculiarities of the functioning of hotel companies require, as, in the end, all companies of the intangible sphere, a special form of interaction with management through the formation of a system of information and communication support. The hospitality industry is a very information intensive industry. The characteristics of business processes of hotel enterprises make it possible to structure functioning both as a function of the technical and technological process, and depending on the time factor, which requires systematic and dynamic information support. The analysis of the latest research on the information support of managerial interactions shows that the emphasis in this direction is on management technology and the relationship between the levels and stages of the management system. The structure, forms, methods and mechanisms of managing business processes through information interaction are ignored. In the course of research, observations and analysis, the reservation processes and components necessary to connect the reservation system to other systems needed in the hotel were considered. The analysis and determination of project requirements, the rationale for the development and implementation of the system was carried out. The planning of project solutions was carried out, the most important planning processes were determined, and the types of interrelationships of operations were determined. The results of the project implementation, compliance with the requirements, and the procedure for completing the project are described.